Synthesis and characterization of Folic acid conjugated Silver/Gold Nanoparticles for Biomedical Applications. (2016) - Vanitha Kumari, G.; Ananth, Nimrodh; Asha,; Mathavan, T.; Jothi Rajan, M.A.
Abstract: Bimetallic Silver/Gold nanoparticles were prepared through chemical reduction in aqueous solution, following a method that was affable to the environment, allowing us to use this for medical purposes. AgNO3 and HAuCl4 were reduced using in-situ techniques in the presence of pectin and folic acid. Using the optical properties of metallic nanoparticles, surface plasmon resonance of metal nanoparticles was determined by UV-Vis spectroscopy, and the values acquired for silver and gold were found to be approximately 350 nm and 530 nm in wavelength respectively. The absorption peaks of the surface plasmon band shows a shift due to the size of the nanoparticles. The average hydrodynamic diameter and the size distribution of the synthesized nanoparticles achieved from dynamic light scattering technique. The folic acid conjugated Ag nanoparticles morphology are gathered by scanning electron microscopy (SEM), functional group by Fourier transform infrared (FTIR) spectroscopy respectively. The development of this process, which is gentle for the environment, opens the possibility for numerous applications in the areas of biomedical applications.